(untitled) (Andamios, Revista de Investigación Social, 2025)
The term collective memory was coined a century ago by Maurice Halbwachs in the framework of sociology of memory, although it was in the field of Memory Studies that the notion experienced its greatest development. In response to the current call for a recover of the sociological foundations and conceptual purity of the term, we argue that the betrayals of its original meaning and context endowed it with the necessary plasticity to productively confront contemporary discussions. To demonstrate this hypothesis, I present two relevant contributions to the concept that, by modifying its original meaning, allowed it to be updated from the perspective of memory studies. As a result, I conclude that the sociological recovery of the term completes but does not exhaust its potential.